Analisis Pengaruh Retrebusi Jasa Umum Retrebusi Jasa Usaha Dan Restrebusi Perijinan Tertentu Terhadap Pendapatan Asli Daerah Kabupaten Alor Periode 2018-2023 - Jafar, Rusmini; Maro, Yustina; Tang, Sefnat Aristarkus; Sabu, Junius Menase Sau (Peneliti.net, 2023)
Regional Original Revenues are all revenues obtained from sources owned by the region which are collected based on regional regulations in accordance with statutory regulations. Regional original income comes from regional levies, regional taxes, results of separated regional wealth management, and other legitimate PAD. This study aims to determine the effect of public service fees, business service fees and license fees on local revenue in Alor Regency for the 2018-2022 period. This type of research is qualitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses secondary data and samples are reports of Local Own Revenue and reports on General Service Fees, Business Service Fees and Certain Permit Fees in the Alor Regency area in 2018-2022. The statistical method used in this study is multiple linear regression by looking at the significant value of the test t and the significant value of the F test as a benchmark in the hypothesis. The results of this study indicate that: 1). partially the general service charge variable has a significance value of 0.011 or 1.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the general service charge variable partially has a positive effect on Original Income Alor Regency Region 2018-2022 Period. 2). partially the Business Services Retribution variable has a significant value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the Business Services Retribution variable has a partial positive effect on Revenue Original area of Alor regency. 3). partially the variable of certain Permit Retribution has a significant value of 0.014 or 1.4% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the variable Permit Retribution partially has a positive effect on Regional Original Income District of Alor. 4). Simultaneously, the variable general service fees, business service fees and certain license fees has a significant value of 0.000 or 0.0%, where this value is smaller than the alpha value, which is 0.05, which is 5%. So that the results of this study simultaneously accept hypothesis 4 which states that the variables of general service fees, business service fees and certain license fees simultaneously have a positive effect on regional original income in Alor Regency.